THE LIFE OF ABDULLAH QADIRI AND HIS CONTRIBUTION TO THE JADID MOVEMENT - Pulatov Jalil Abdisalom oglu (Galaxy International Interdisciplinary Research Journal, 2021)
The article tells about the life and work of Abdullah Qadiri, the founder of Uzbek novels, as well as about his work and his role in Jadidism.